The Effect of Project-Based Learning with Realistic Mathematics Approach on Students Self-regulated learning - Fujiarti, Ari; Prabawanto, Sufyani (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2021)
This study aims to find out how the effect of the project-based learning model with a realistic mathematics education approach on students' self-regulated learning independence. This research was a quasi-experimental study with a non-equivalent control group design. The population of this study was all fifth-grade students of the public elementary school in the Sumedang Utara district, Sumedang Regency. The sample in this study was the fifth-grade students from two public elementary schools in the Sumedang Utara district, Sumedang Regency. Fifth-grade students from one public elementary school were designated as the experimental group, whereas fifth-grade students from another public elementary school were designated as the control group. The instruments in this study were a self-regulated learning scale using a Likert scale, observation guidelines, student daily journals, and field notes. The results of this study indicate that with a significance level of = 0.05 (5%) the project-based learning model with the Realistic Mathematics Education approach can improve students self-regulated learning